(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Anemia in pregnancy is at risk for LBW, miscarriage, premature birth, bleeding and mortality for mother and baby. This study purposed to determine the causes of pregnant women anemia in rural and urban of Banyumas regency. This study was a cross sectional with 135 sample, 60 women at Baturaden I Health Center and 75 women at East Purwokerto Health Center II. The research variables were gestational age, nutritional status, maternal age, birth spacing, number of children, nutrient intake, iron intake and knowledge. Hb levels measured by the cyanmethemoglobin. Food intake and consumption patterns using the Frequency Questionnaire. Data analysis using Chi-Square and multiple logistic regression. The results showed that anemia in urban (50.7%) was higher than rural (38.3%). The causes of anemia in rural are maternal age, gestational age, birth spacing, Fe tablet consumption and enhancer consumption patterns with the main cause maternal age. The causes of anemia in urban are protein intake, gestational age, vitamin C intake and Fe tablet consumption with the main cause maternal gestational age. There are the same two factors, gestational age and consumption of Fe tablets. To prevent anemia, it’s necessary to improve eating patterns and adherence to taking Fe tablets.